Transgender`s rights analysis from Islamic jurisprudential perspective - Haneef, Sayed Sikandar Shah (2013)
The question of transgender rights is a much emotionally charged issue particularly in the local scene. In this presentation, I try to briefly outline the position of Islamic law in the context of what characterizes trans-people in Malaysia(Muslim ones).